Effects of Oil Contamination on Range of Soil Types in Middle Taiga of Western Siberia - Oleg S. Sutormin; Andrey S. Goncharov; Valentina A. Kratasyuk; Yuliya Yu. Petrova; Ruslan Ya. Bajbulatov; Aleksandr E. Yartsov; Aleksandr A. Shpedt (Sustainability, 2024)
This study examines the effects of oil contamination on three soil types—podzolic, sod-gley, and alluvial—in Western Siberia’s middle taiga, assessing key physical and chemical properties and the influence of the surfactant Modified Syntherol (MS) on oil degradation. In controlled laboratory experiments, oil was introduced at 50, 100, and 150 g/kg concentrations. Results indicate a substantial increase in soil pH, most notably in podzolic soils, alongside a significant decline in cation exchange capacity (CEC). For example, CEC in podzolic soils dropped five-fold at higher contamination levels, reflecting a reduced ability to retain essential nutrients. The water retention capacity decreased in all soil types, with the most pronounced decline observed in alluvial soils’ capillary moisture levels. MS application did not accelerate oil degradation; even after 35 days, natural decomposition rates in untreated soils remained low (0.02–0.4%), underscoring the persistence of oil contaminants. Notably, podzolic soils showed the highest susceptibility to oil contamination due to their acidic and low-organic nature, in contrast to sod-gley and alluvial soils, which demonstrated moderate resilience. These findings highlight the need for soil-specific remediation approaches, as general methods may be ineffective for soils with differing vulnerabilities and recovery capacities. This research provides essential insights for developing effective, tailored strategies to address the environmental challenges of oil pollution, advancing sustainable soil management practices for sensitive taiga ecosystems.